Dengue incidence and length of viremia by RT-PCR in a prospective observational community contact cluster study from 2005-2009 in Indonesia. - Silvita Fitri Riswari; Dyana Safitri Velies; Nurhayati Lukman; Ungke Anton Jaya; Hofiya Djauhari; Chairin Nisa Ma'roef; Khin Saw Aye Myint; Susana Widjaja; Andre van der Ven; Bachti Alisjahbana; Quirijn de Mast; Herman Kosasih (Public Library of Science (PLoS), 2023)
Background Dengue has become a major global health threat since being recognized three centuries ago. Important gaps remain in understanding the transmission dynamics of dengue virus (DENV) infection. This study reports the results of a prospective observational cluster study that investigated the incidence of symptomatic and asymptomatic infections and length of viremia among close community contacts of hospitalized DENV-infected patients. Methodology/principal findings Between 2005 and 2009, dengue-confirmed cases (n = 97) admitted to Hasan Sadikin Hospital in Bandung, Indonesia, were enrolled as index cases. Subsequently, twenty close community contacts (n = 1928) living with and around the index cases were included and followed up for up to 14 days. Body temperature was measured daily; blood samples were collected every 3-4 days and when reported fever. DENV infection was confirmed using Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR), IgM rapid test, and Enzyme-linked Immunosorbent Assay (ELISA). Among the 1928 community contacts, a total of 72 (3.7%) acute DENV infections were diagnosed, which equates to an incidence of 636 cases per 1,000 person-years (95% Confidence interval (CI) 588 to 687 cases per 1,000 person-years). Twenty-nine cases (40%) were symptomatic (22 dengue fever (DF) & 7 dengue hemorrhagic fever (DHF)), and 43 (60%) were asymptomatic. Primary and secondary DENV infections were detected in 18 (25%) and 54 (75%) subjects. Among the RT-PCR positives, viremia was observed as early as seven days before fever onset and converted to negative as late as seven days after the onset of fever. Conclusions DENV infections are common among close community contacts of hospitalized dengue patients. The high number of asymptomatic infections and the observation that viremia precedes the onset of fever for up to seven days highlight the importance of unrecognized dengue transmission and the need for improved transmission control.